Human Nature, Ethics, and Moral Education: A Philosophical Reading of Murtadha Muthahhari’s Thought - Mukim Mukim; Abdul Aziz (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The growing fragmentation of moral values in contemporary education has renewed philosophical interest in educational paradigms that integrate ethical formation with human development. This article reconstructs Murtadha Muthahhari’s philosophy of moral education as an integrated educational paradigm through Gadamerian philosophical hermeneutics. Employing qualitative library research, the study analyzes Muthahhari’s principal works through dialogical interpretation,historically effected consciousness, and the fusion of horizons to reconstruct the conceptual architecture underlying his educational philosophy. The hermeneutic reconstruction demonstrates that Muthahhari’s paradigm is organized around the integration of fitrah, reason ('aql), freedom, moral responsibility, and kamāl (human perfection), forming a coherent philosophical framework that unites ontology, anthropology, ethics, and spirituality. Rather than reducing moral education to value transmission or behavioral regulation, this framework conceives education as the cultivation of ethical subjectivity through the actualization of humanity’s innate moral potential. The article advances existing scholarship by establishing the internal coherence of Muthahhari’s educational philosophy beyond fragmented theological, ethical, and ideological interpretations. It further demonstrates the explanatory power of Gadamerian hermeneutics for reinterpreting classical Islamic educational thought within contemporary educational philosophy, thereby providing a philosophically grounded framework for addressing moral fragmentation, character formation, and the ethical purpose of education in pluralistic societies.